PENGARUH PENGETAHUAN DAN SIKAP PERAWATTERHADAP STANDAR KESELAMATAN PASIEN DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAHARIFIN ACHMAD PROVINSI RIAU - Lilik istikhairyah; Marian Tonis, Anastasya Shinta Yuliana, Agus Salim (Jurnal Kesehatan, 2024)
Patient safety standards include efforts to improve patient safety, namely being able to educate staff about patient safety and communication being the key to patient safety. The research used was quantitative research with a sample size of 38 nurses in inpatient wards and the sampling technique in this research used Probability Sampling. Meanwhile, to determine the sample to be studied using Simple Random Sampling. The results of the research show that knowledge and attitudes have a significant effect on patient safety standards in the inpatient room atthe Arifin Achmad Regional General Hospital. This is supported by the F test which shows that the significance value is 0.000 which is smaller than 0.05, which means that Accurate patient identification, Increased effective communication, Increased safety of drugs that need to be alert (high-alert), Certainty of the right location, rightprocedure, right patient operation, Reduction of the risk of health care related infections and Reduction of the risk of patient falls all together (simultaneous) has a significant influence on Knowledge and Attitude. The conclusion of this research is that knowledge and attitudes have a significant effect on patient safety standards in the inpatient room at the Arifin Achmad Regional General Hospital. This is supported by the F test which shows that the significance value is 0.000 which is smaller than 0.05, which means that these variables together (simultaneously) have a significant influence on Knowledge and Attitude. The suggestion of this research is to further improve patient safety standards both in the inpatient room and all services in the hospital.